2001
DOI: 10.1177/000348940111001016
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Level I Neck Lymph Nodes in Advanced Squamous Carcinoma of the Larynx

Abstract: This study was performed to evaluate the incidence of metastasis at level I in patients with squamous laryngeal cancer. One hundred consecutive patients with squamous carcinoma of the larynx were submitted to surgical treatment including radical neck dissection. The tumor stage was T3 or T4, and the neck stage was N1-N2c. Lymph node metastases were pathologically confirmed in 80 patients. Metastases were concentrated within level II in 59% of cases, level III in 17% of cases, level IV in 11% of cases, and leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 17 publications
4
20
0
Order By: Relevance
“…Dos Santos CR et al [17] found that lymph node metastasis was seen in 80 patients with advanced squamous cell carcinoma of larynx, out of which metastases were concentrated within level II in 59% of cases, level III in 17% of cases, level IV in 11% of cases and level V in 6% of cases. Most patients presented with T3 stage present in 48 (43.63%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…Dos Santos CR et al [17] found that lymph node metastasis was seen in 80 patients with advanced squamous cell carcinoma of larynx, out of which metastases were concentrated within level II in 59% of cases, level III in 17% of cases, level IV in 11% of cases and level V in 6% of cases. Most patients presented with T3 stage present in 48 (43.63%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Hamoir et al [8] proposed that it might not be necessary to dissect the superior portion of level VA in most patients with head and neck cancer. Lastly, dos Santos et al [9] showed that level I is rarely affected in carcinoma of the larynx, even at advanced stages, and thus it need not be dissected unless clinical evidence of disease is present. It is this author's opinion that continued modifications of the standardized neck dissections (ie, leaving level IIB behind in a supraomohyoid neck dissection) often make the dissection more difficult because they require well-defined anatomic planes and boundaries and increase the risk of leaving occult disease behind.…”
Section: Nodal Groupsmentioning
confidence: 99%
“…Oropharyngeal , hypopharyngeal and laryngeal cancers are at highest risk for nodal metastases to regions II -IV, which are adequately encompassed by a lateral (jugular) neck dissection (LND). Recent data, although retrospective in nature, show that patients with squamous cell carcinoma of the larynx rarely present metastases at the submandibular triangle, or level IB (only 2%), even in advanced local disease with cervical metastases staged as N1 -N2c (49). Two recent prospective studies support the use of LND for N0 laryngeal and hypopharyngea l cancers (6) and supraglottic and transglottic cancers (41).…”
Section: Patterns Of Lymphatic Metastasesmentioning
confidence: 99%